Analisis Konsep Strategi dalam Perencanaan Pendidikan Islam - Khildah Salsabilatun Najah (Al-Kindi, 2026)
Islamic education planning is a strategic process aimed at directing educational implementation in accordance with Islamic values and responding to contemporary challenges. This article analyzes the concept of strategy in Islamic education planning, including the basic concept of strategy, stages of implementation, factors influencing strategic application, and challenges in its implementation. This study employs a qualitative approach using a library research method by reviewing relevant literature such as books, scholarly journals, and academic works. The analysis shows that strategy in Islamic education planning is a comprehensive framework that links educational goals with operational actions. The strategic stages include analyzing the institution’s current conditions, determining strategic directions and objectives, and formulating implementation steps accompanied by monitoring and evaluation. The success of strategy implementation is influenced by internal factors, such as the quality of human resources, organizational culture and structure, and facilities, as well as external factors, including socio-cultural changes, technological developments, government policies, and stakeholder support. In addition, the implementation of strategic planning in Islamic education faces challenges such as resistance to change, limited resources, environmental complexity, weak leadership, and difficulties in performance evaluation. Therefore, adaptive and sustainable strategic planning is essential to achieve the goals of Islamic education optimally.